Productivity and profitability of rapeseed as influenced by irrigation depth and irrigation scheduling based on can-evaporimeter (Journal of Oilseed Brassica, 2026)
The effects of irrigation depth and irrigation scheduling on productivity and profitability of rapeseed was studied during Rabi 2018-19. Nine treatment combinations of three irrigation depths viz., 4 cm (I1), 5 cm (I2) and 6 cm (I3) and three irrigation schedules viz., irrigation at 4 cm (D1), 5 cm (D2) and 6 cm (D3) evaporation from a can-evaporimeter were laid out in factorial randomised block design with three replications. Irrigation of 6 cm depth recorded the highest values of growth parameters like plant height, total dry matter accumulation, leaf area index and yield attributing characters viz. number of branches per plant, number of siliquae per plant and number of seeds per siliqua which is, in turn, resulted in higher seed and stover yields as well. Similarly, irrigation scheduled at 4 cm evaporation from can-evaporimeter resulted in highest yield attributing characters, seed yield and stover yield. Among the different treatment combinations, irrigation of 6 cm depth scheduled at 4 cm evaporation (I3D1) recorded the maximum seed and stover yields, gross returns (Rs. 41510/ha), net returns (Rs. 14322/ha) and B:C ratio (1.53).